Learning Curve for Laparoscopic Hysterectomy: An Experience from Kathmandu University Hospital - Tamrakar, Suman Raj; Pradhan, N.; Kayastha, Suresh (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of this study is to assess learning curves for laparoscopic hysterectomies, compare the performance of surgeons and review demographic parameters of the patients, varieties of complications experienced and indications of the procedures. Methods: A retrospective study was conducted in Kathmandu University Hospital, Kavre of January 1, 2011 to June 30, 2018. Results: A total of 1849 cases were already performed by mid 2018. Of them, 261 (14.12%) cases were LAVH and TLH cases. Mean duration for laparoscopic hysterectomies (for both LAVH and TLH) was 142.21±43.46 minutes (range 55 to 310 minutes) and one third of the cases performed in a range of 121 to 150 minutes. There is difference in mean duration of operation between surgeons which is statistically significant (p